1992
DOI: 10.1161/01.res.71.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of endothelium-dependent relaxations to bradykinin by angiotensin I converting enzyme inhibitors in canine coronary artery involves both endothelium-derived relaxing and hyperpolarizing factors.

Abstract: Studies were designed to investigate the mechanisms underlying the augmentation by angiotensin I converting enzyme (ACE) inhibitors of the endothelium-dependent relaxations evoked by bradykinin. Isometric tension, tissue levels of cGMP, and transmembrane potential were measured in isolated canine coronary arteries as indications of the respective contribution of nitric oxide and endothelium-derived hyperpolarizing factor. In rings of coronary artery with endothelium, relaxations to bradykinin were potentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
2
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(104 citation statements)
references
References 35 publications
5
96
2
1
Order By: Relevance
“…24 -26 In the present in vivo study, we found that proadifen completely eliminated the remaining vasodilator response of juxtamedullary afferent arterioles observed during the inhibition of angiotensin II and NO. These findings therefore are compatible with previous in vitro observations that a part of the ACE inhibitor-induced vasodilation is associated with EDHF 27,28 and further allow extrapolation to the in vivo actions of this agent. Caveat is in order, because proadifen is reported to inhibit the K channel activity and the cytochrome P450-mediated EDHF production.…”
Section: Discussionsupporting
confidence: 91%
“…24 -26 In the present in vivo study, we found that proadifen completely eliminated the remaining vasodilator response of juxtamedullary afferent arterioles observed during the inhibition of angiotensin II and NO. These findings therefore are compatible with previous in vitro observations that a part of the ACE inhibitor-induced vasodilation is associated with EDHF 27,28 and further allow extrapolation to the in vivo actions of this agent. Caveat is in order, because proadifen is reported to inhibit the K channel activity and the cytochrome P450-mediated EDHF production.…”
Section: Discussionsupporting
confidence: 91%
“…13 In vitro, the bradykinin-induced vasorelaxation is potentiated by ACE inhibitors. 24 In humans, bradykinin is involved in the vascular effect of ACE inhibitors. 25 A recent study from our laboratory has shown that enalaprilat extends the duration of the effect of bradykinin with no significant changes in the peak CBFv response to bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, restoration of nitric oxide generation by either the administration of the substrate L-arginine 12 or treatment with angiotensin-converting enzyme (ACE) inhibitors results in a lowering of blood pressure. 13 These by guest on May 11, 2018 http://hyper.ahajournals.org/ Downloaded from data indicate that the regulation of nitric oxide generation by the endothelium may be a critical determinant of blood pressure in hypertension. Advances in vascular biology have also reshaped our understanding of previously characterized classic hormonal systems.…”
Section: Novel Autocrine-paracrine Mediators Of Hypertensionmentioning
confidence: 97%